2020
DOI: 10.1111/ejn.15031
|View full text |Cite
|
Sign up to set email alerts
|

C‐Reactive Protein: Marker of risk for post‐traumatic stress disorder and its potential for a mechanistic role in trauma response and recovery

Abstract: Increasing evidence indicates that inflammation plays a role in PTSD and stress disorder pathophysiology. PTSD is consistently associated with higher circulating inflammatory protein levels. Rodent models demonstrate that inflammation promotes enduring avoidance and arousal behaviors after severe stressors (e.g., predator exposure and social defeat), suggesting that inflammation may play a mechanistic role in trauma disorders. C-reactive protein (CRP) is an innate acute phase reactant produced by the liver aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 181 publications
(183 reference statements)
2
16
1
2
Order By: Relevance
“…Previous literature exists on association between PTSD and elevated inflammatory biomarkers. 25 Although most our patients suffered a relatively mild stroke, or even a TIA, the prevalence of probable PTSD within 1 year of the stroke was 11%, in line with previously published reports. 26 Stroke was more likely to cause PTSD than TIA.…”
Section: Discussionsupporting
confidence: 91%
“…Previous literature exists on association between PTSD and elevated inflammatory biomarkers. 25 Although most our patients suffered a relatively mild stroke, or even a TIA, the prevalence of probable PTSD within 1 year of the stroke was 11%, in line with previously published reports. 26 Stroke was more likely to cause PTSD than TIA.…”
Section: Discussionsupporting
confidence: 91%
“…Since evidence suggests a relationship of psychosocial stress and psychiatric disorders with low-grade systemic inflammation ( 8 ), CRP levels are examined by a growing body of research in this field. A variety of studies confirms an association of elevated CRP with depressive symptoms ( 9 13 ), post-traumatic stress disorder (PTSD) ( 14 , 15 ), and psychosis ( 16 18 ) as well as with perceived psychosocial stress ( 19 ) in adults. Positive affect, in turn, is considered to be negatively associated with CRP and to buffer against stress-related increases in CRP levels ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 97%
“…Another well-studied inflammatory marker is CRP. Studies have shown a positive correlation between CRP and PTSD where individuals with PTSD showed increased CRP levels compared to healthy controls [73,78,80,81]. However, mixed results were observed in different PTSD cohorts.…”
Section: Inflammation and Ptsdmentioning
confidence: 99%